Complications of mechanical thrombectomy for acute ischemic stroke: Incidence, risk factors, and clinical relevance in the Italian Registry of Endovascular Treatment in acute stroke. Issue 7 (October 2021) - Salsano, Giancarlo; Pracucci, Giovanni; Mavilio, Nicola; Saia, Valentina; Bandettini di Poggio, Monica; Malfatto, Laura; Sallustio, Fabrizio; Wlderk, Andrea; Limbucci, Nicola; Nencini, Patrizia; Vallone, Stefano; Zini, Andrea; et al.
Background: There are limited data concerning procedure-related complications of endovascular thrombectomy for large vessel occlusion strokes. Aims: We evaluated the cumulative incidence, the clinical relevance in terms of increased disability and mortality, and risk factors for complications. Methods: From January 2011 to December 2017, 4799 patients were enrolled by 36 centers in the Italian Registry of Endovascular Stroke Treatment. Data on demographic and procedural characteristics, complications, and clinical outcome at three months were prospectively collected. Results: The complications cumulative incidence was 201 per 1000 patients undergoing endovascular thrombectomy. Ongoing antiplatelet therapy (p < 0.01; OR 1.82, 95% CI: 1.21–2.73) and large vessel occlusion site (carotid-T, p < 0.03; OR 3.05, 95% CI: 1.13–8.19; M2-segment-MCA, p < 0.01; OR 4.54, 95% CI: 1.66–12.44) were associated with a higher risk of subarachnoid hemorrhage/arterial perforation. Thrombectomy alone (p < 0.01; OR 0.50, 95% CI: 0.31–0.83) and younger age (p < 0.04; OR 0.98, 95% CI: 0.97–0.99) revealed a lower risk of developing dissection. M2-segment-MCA occlusion (p < 0.01; OR 0.35, 95% CI: 0.19–0.64) and hypertension (p < 0.04; OR 0.77, 95% CI: 0.6–0.98) were less related to clot embolization. Higher NIHSS at onset (p < 0.01; OR 1.04, 95% CI: 1.02–1.06), longer groin-to-reperfusion time (p < 0.01; OR 1.05, 95% CI: 1.02–1.07), diabetes (p < 0.01; OR 1.67, 95% CI: 1.25–2.23), and LVO site (carotid-T, p < 0.01; OR 1.96, 95% CI: 1.26–3.05; M2-segment-MCA, p < 0.02; OR 1.62, 95% CI: 1.08–2.42) were associated with a higher risk of developing symptomatic intracerebral hemorrhage compared to no/asymptomatic intracerebral hemorrhage. The subgroup of patients treated with thrombectomy alone presented a lower risk of symptomatic intracerebral hemorrhage (p < 0.01; OR 0.70; 95% CI: 0.55–0.90). Subarachnoid hemorrhage/arterial perforation and symptomatic intracerebral hemorrhage after endovascular thrombectomy worsen both functional independence and mortality at three-month follow-up (p < 0.01). Distal embolization is associated with neurological deterioration (p < 0.01), while arterial dissection did not affect clinical outcome at follow-up. Conclusions: Complications globally considered are not uncommon and may result in poor clinical outcome. Early recognition of risk factors might help to prevent complications and manage them appropriately in order to maximize endovascular thrombectomy benefits.